Latitude as a Factor Influencing Variability in Vegetational Development in Northeast England During the First (Preboreal) Holocene Millennium - J. B. Innes; C. Orton (Quaternary)
In the North Atlantic region, the transition from the very cold Lateglacial Stadial (GS-1) to the temperate Holocene was abrupt, with a rapid increase in temperature of several degrees, after which the low-stature, cold-tolerant Stadial vegetation was replaced through the immigration and rapid succession of tall herb, heath, and shrub communities towards Betula woodland of varying density. In northeast England, pollen diagrams on a south to north transect between mid-Yorkshire and the Scottish border show that there was considerable variation in the rate at which postglacial woodland was established in the first Holocene millennium. In mid-Yorkshire’s Vale of York, the development of closed Betula woodland was swift, whereas in north Northumberland, near the Scottish border, Betula presence was low for the first several centuries of the Holocene, with open vegetation persisting and with shrub vegetation dominated mostly by Juniperus. Intermediate locations on the transect show there was a gradient in post-Stadial vegetation development in northeast England, with latitude as a major factor, as well as altitude. Transitional locations on the transect have been identified, where vegetation community change occurred. Vegetation development in the first Holocene millennium in northeast England was spatially complex and diverse, with the climatic effects of latitude the main controlling environmental variable.